2016
DOI: 10.3167/aia.2016.230303
|View full text |Cite
|
Sign up to set email alerts
|

Place of Birth and Concepts of Wellbeing

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Unit -FMU). Midwifery units have been designed and intended specifically as locations of wellbeing and although the meaning of the term is used very loosely in public discourse, this claim is supported by a large epidemiological study, which found that they provide safe care for babies while reducing use of medical interventions and with better health outcomes for the women. Our research indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Since publication of the overall study report (McCourt et al 2014) service managers and commissioners have raised concerns in personal communications and public forums about sustaining provision, and around optimum staffing models. Issues relating to women's experiences in relation to information and access will be published elsewhere, while women's and midwives' experiences of MU care have been reported in earlier publications (McCourt et al 2016).…”
Section: Aims and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since publication of the overall study report (McCourt et al 2014) service managers and commissioners have raised concerns in personal communications and public forums about sustaining provision, and around optimum staffing models. Issues relating to women's experiences in relation to information and access will be published elsewhere, while women's and midwives' experiences of MU care have been reported in earlier publications (McCourt et al 2016).…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…While the development of AMUs was generally achieved as part of wider service redesign, midwifery managers on all sites had a clear view of the proposed philosophy of the unit and its aims to provide a more homely birth environment that would be woman-and family-centred and facilitate normal physiological birth practices, and midwife-led care for low-risk women. In effect, the managers and consultant midwives developing these units were engaged in materialising a philosophy of birth as a biopsychosocial event (Jordan 1992, McCourt et al 2016,…”
Section: Setting Up the Amumentioning
confidence: 99%
“…25 They are also more cost-effective than AMUs in relation to the primary outcome of neonatal adverse outcome and the secondary outcome of maternal morbidity, although this is reduced if only low-risk women without complications at the onset of labour are compared. 46 In addition, organisational research has found that midwifery satisfaction is very high in these settings 95 and they are much less prone to problems of staff recruitment and retention, which are a contemporary challenge to the sustainability of the maternity workforce. 96 The aim of this part of the project was to explore what an analysis of media coverage of the closure of FMUs might tell us about the reasons given for the closures, how are these closures presented publicly and by whom, and whether media representations support or disrupt pervading cultural norms around place of birth in England.…”
Section: Media Analysismentioning
confidence: 99%
“…low birth numbers in a FMU) without examining how this could be addressed collaboratively. Douglas's theory 163 of grids and groups in organisation refers to enclaves: autonomous, non-hierarchical small spaces, which McCourt et al 95 liken to MUs. Though enclaves can create a therapeutic space in which both staff and clients can flourish, they tend to have an uneasy relationship with their host organisations, which operate hierarchically.…”
Section: Institutional Controlmentioning
confidence: 99%
See 1 more Smart Citation